The implementation of a municipal indoor ice skating helmet policy: effects on helmet use, participation and attitudes. Issue 6 (18th May 2015) - O'Mahony-Menton, Colleen; Willmore, Jacqueline; Russell, Katherine
Abstract : Relevant local injury epidemiology: In Ottawa, between 2005 and 2009 there was an annual average of 47.2 head injuries due to ice skating in children and youth (1–19 years of age) requiring a visit to the emergency department, with the highest rates among those aged 5–14 years. Between 2002 and 2007, only 6% of children were wearing a helmet during ice skating when the head injury occurred. During indoor public skating sessions, 93% of children (<10 years)—57% aged 10–12 years, 20% aged 13–17 years and 9% adults—wore helmets in the absence of a policy. Support for a helmet policy was high from public health, medical, political and community perspectives. Best practice: Helmet policies in relation to cycling have demonstrated increases in helmet use and reduction of head injuries without decreasing physical activity. However, no known studies have examined the effect of indoor ice skating helmet policy coupled with education and promotional activities on helmet use, participation and attitudes towards helmet use. Implementation: An ice skating helmet policy for children (<11 years of age) and those with limited skating experience at indoor rinks during public skating sessions was developed, implemented and evaluated. Supportive activities such as discount coupons, promotional materials, a media launch, social marketing and staff training are described. Discussion: The helmet policy was associated with increased helmet use for young children and for older children, youth and adults not included in the policy, without decreasing attendance to public skating sessions.